ETIKA KOMUNIKASI DI ERA DIGITAL : (TINJAUAN HADITS TENTANG ADAB BERBICARA) - Mumtaz Muizza, Muhammad Ahmad; Sholahuddin Al Ayubi (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2024)
This study examines communication ethics in the digital era from the perspective of Islamic teachings, focusing on the influence of digital communication on language values ​​and morals. Using qualitative methods with literature studies, this study analyzes hadiths related to social ethics, as narrated by Abu Daud, to emphasize the importance of maintaining speech and behavior in interactions. The phenomenon of the crisis in understanding ethics in the use of language on social media shows that people's understanding of ethics and linguistic values ​​is still low. The findings show that good communication ethics are needed to prevent negative practices such as cyberbullying, hoaxes, and hate speech, as well as to build a more ethical online environment. In addition, the hadith that reminds us of the dangers of uttering sentences without careful thought emphasizes the need for caution in conveying information. Therefore, this study provides recommendations to improve the understanding of communication ethics among social media users, in order to create more constructive and meaningful interactions in communication.